The natural history of temporal variant frontotemporal dementia - Seeley, W.W. (2005)
BACKGROUND: The temporal variant of frontotemporal dementia (tvFTD) features asymmetric anterior temporal/amygdala degeneration as well as ventromedial frontal, insular, and inferoposterior temporal involvement. Left temporal atrophy has been linked to loss of semantic knowledge, whereas behavioral symptoms dominate the right temporal variant. OBJECTIVE: To investigate the first symptoms and the timing of subsequent symptoms in patients with left versus right tvFTD. METHODS: Twenty-six patients with tvFTD were identified. Six had right > left temporal atrophy (right temporal lobe variant [RTLV]) and were matched with six having comparable left > right temporal atrophy (left temporal lobe variant [LTLV]). Clinical records were reviewed to generate individualized symptom chronologies. RESULTS: In all patients, first symptoms involved semantics (4/6 LTLV, 1/6 RTLV), behavior (4/6 RTLV, 1/6 LTLV), or both (1 LTLV, 1 RTLV). Semantic loss began with anomia, word-finding difficulties, and repetitive speech, whereas the early behavioral syndrome was characterized by emotional distance, irritability, and disruption of physiologic drives (sleep, appetite, libido). After an average of 3 years, patients developed whichever of the two initial syndromes—semantic or behavioral—that they lacked at onset. A third stage, 5 to 7 years from onset, saw the emergence of disinhibition, compulsions, impaired face recognition, altered food preference, and weight gain. Compulsions in LTLV were directed toward visual, nonverbal stimuli, whereas patients with RTLV were drawn to games with words and symbols. CONCLUSIONS: The temporal variant of frontotemporal dementia follows a characteristic cognitive and behavioral progression that suggests early spread from one anterior temporal lobe to the other. Later symptoms implicate ventromedial frontal, insular, and inferoposterior temporal regions, but their precise anatomic correlates await confirmation.